Rewarding Safer Sex : Conditional Cash Transfers for HIV/STI Prevention - de Walque, Damien (World Bank Group, Washington, DC, 2014)
Incentive-based policies have been shown to be powerful in many areas of behavior, but have rarely been tested in the sexual domain. The Rewarding Sexually Transmitted Infection Prevention and Control in Tanzania (RESPECT) study is a randomized controlled trial testing the hypothesis that a system of rapid feedback and positive reinforcement that uses cash as the primary incentive can be used to reduce risky sexual activity among young people, male and female, who are at high risk of HIV infection. The study enrolled 2,399 participants in 10 villages in rural southwest Tanzania. The intervention arm received conditional cash transfers that depended on negative results of periodic screenings for sexually transmitted infections, an objectively measured marker for risky sexual behavior. The intervention arm was further divided into two subgroups, one receiving a high value payment of up to $60 over the course of the study ($20 payments every four months) and the other receiving a lower value payment of up to $30 ($10 payments every four months). At the end of the one year of intervention, the results showed a significant reduction in sexually transmitted infections in the group that was eligible for the $20 payments every four months, but no such reduction was found for the group receiving the $10 payments. The effects were stronger among the lower socioeconomic and higher risks groups. The results of a post-intervention follow-up survey conducted one year after discontinuing the intervention indicate a sustained effect among males, but not among females.